Oral Polio Vaccine: An Evolution - DrPrasanna Kumar Sahoo, GangadharSahoo, Bhagirathi Kar (International Journal of Advanced Science and Technology, 2020)
The intense disease in poliomyelitis brought about by 3 polio infection serotypes 1,2,3 and it was the main source of lasting inability in children in the pre-immunization time. Practically all children got contaminated by Polio infection by feco-orally or oro-orally. Feco-oral transmission is dominating in poor sanitation condition whereas oral transmission is more where benchmarks of sanitation are high. Blended examples of transmission normally happen in many settings. On normal 1 out of 200 susceptible people developedParalytic Poliomyelitis3